2014
DOI: 10.1007/s40135-014-0046-4
|View full text |Cite
|
Sign up to set email alerts
|

Management of Acute Conjunctivitis

Abstract: Acute conjunctivitis can be caused by viral, bacterial, and allergic sources. There is growing need for rapid diagnostics and effective therapies given the significant economic burden and pervasive nature of the disease. Additionally, with growing microbial resistance, practice guidelines should encourage appropriate use of antibiotics, limited to clinical situations with proven benefit. New inoffice detectors may enable rapid definitive diagnosis among clinically similar entities. Development of and studies e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(50 citation statements)
references
References 77 publications
1
49
0
Order By: Relevance
“…Several studies reported a seasonal increase in the incidence of conjunctivitis cases, especially in spring and summer periods. This can be attributed to the known seasonal high transmission of some aetiological pathogens, or to allergic conjunctivitis which has a relatively higher incidence in spring [Saitoh-Inagawa et al, 1999;Marangon et al, 2007;Matsui et al, 2007;Sambursky et al, 2007;La Rosa et al, 2011;Segal et al, 2014;Erdin et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported a seasonal increase in the incidence of conjunctivitis cases, especially in spring and summer periods. This can be attributed to the known seasonal high transmission of some aetiological pathogens, or to allergic conjunctivitis which has a relatively higher incidence in spring [Saitoh-Inagawa et al, 1999;Marangon et al, 2007;Matsui et al, 2007;Sambursky et al, 2007;La Rosa et al, 2011;Segal et al, 2014;Erdin et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…It can also have an allergic origin and it is difficult to differentiate between the different aetiologies clinically, without detection of the causative agent. [Darougar et al, 1978;Shulman et al, 1997;Madhavan, 1999;Marangon et al, 2007;Aoki et al, 2011;Tavares et al, 2011;Ghebremedhin, 2014;Segal et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…Adenoviruses are most often the cause of acute infectious conjunctivitis. 1,2,4,6,8,9,11 Unfortunately, due to the similarity of presenting clinical symptoms, it is usually misdiagnosed as caused by bacteria. 4,10,12 Presenting symptoms include a high fever, pharyngitis, bilateral conjunctivitis and swelling of the periauricular lymph nodes (pharyngoconjunctival fever) or in more severe cases as hyperaemia, swelling of the conjunctiva, watery discharge and swollen lymph glands (epidemic keratoconjunctivitis).…”
Section: Viral Conjunctivitis (Adenoviruses)mentioning
confidence: 99%
“…This condition is usually selflimiting. [1][2][3][4][6][7][8][9]11 Topical antibiotics are sometimes mistakenly prescribed for this viral infection due to incorrect diagnosis of the causative agent. This not only leads to an increased risk of toxicity and allergies, but also delays the diagnosis of other ocular diseases and increases the risk of resistance developing.…”
Section: Viral Conjunctivitis (Adenoviruses)mentioning
confidence: 99%
See 1 more Smart Citation